2014
DOI: 10.14444/1017
|View full text |Cite
|
Sign up to set email alerts
|

Five and Ten Year Follow-up on Intradiscal Ozone Injection for Disc Herniation

Abstract: BackgroundDisc herniation is the most common cause for spinal surgery and many clinicians employ epidural steroid injections with limited success. Intradiscal injection of ozone gas has been used as an alternative to epidural steroids and surgical discectomy. Early results are positive but long-term data are limited.MethodsOne hundred and eight patients with confirmed contiguous disc herniation were treated with intradiscal injection of ozone in 2002-2003. One-hundred seven patients were available for telephon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 51 publications
4
66
1
4
Order By: Relevance
“…For several decades these properties have prompted its use in orthopedic diseases such as osteoarthritis, arthritis, and herniated discs, [14][15][16] contributing significantly to the reduction in surgical treatment and improving patients' quality of life; moreover, arterial and venous vascular diseases, and metabolic, autoimmune, infectious and neoplastic diseases also benefit from it. 17,18 Ozone induces the repair of tissue damage through the release of several growth factors and by activating the body's own stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…For several decades these properties have prompted its use in orthopedic diseases such as osteoarthritis, arthritis, and herniated discs, [14][15][16] contributing significantly to the reduction in surgical treatment and improving patients' quality of life; moreover, arterial and venous vascular diseases, and metabolic, autoimmune, infectious and neoplastic diseases also benefit from it. 17,18 Ozone induces the repair of tissue damage through the release of several growth factors and by activating the body's own stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Another important analgesic effect may be derived by the induction of antioxidant enzymes resulting in the adaptation to chronic oxidative stress. These novel and surprising aspects have allowed formulating the concept of the ozone-paradox [27,28].…”
Section: Ozone Therapy and Knee Arthritismentioning
confidence: 99%
“…The herniated fragment has to be smaller than 1/3 of the spinal canal. Patients were enrolled in the study from February 2014 to February 2015. all subjects received one intradiscal injection of oxygen-ozone (following the method reported in Buric et al [28]) and eight major ozonated autohaemotherapy two times a week (150 ml of blood + 150 ml of ozone at a concentration of 20 micrograms/ml of gas according to Borrelli et al) [14]. Before and after the last treatment of MOAT we analyzed in all patients the plasma value of Reactive Oxygen were divided in two groups: group 1 (18 rats) received a single intra articular injection of 0.05 ml of monoiodiacetate (MIA), a well-known inflammatory agent, in the right knee, group 2 (18 rats) received in the same articulation 0.05 ml of ozone at dose of 20 micrograms/ml three times a week for a total of 12 injections.…”
Section: Ozone Therapy and Knee Arthritismentioning
confidence: 99%
“…Multiple studies have suggested a low complication rate for this ozone disk nucleolysis, with reported success rates varying from 65 to 80% in different studies. 8 Ozone nucleolysis is being used in multiple countries for over three decades. Leonardi popularized fluoroscopic-guided ozone disk nucleolysis globally.…”
Section: Introductionmentioning
confidence: 99%
“…Leonardi popularized fluoroscopic-guided ozone disk nucleolysis globally. 8,9 Though ozone is toxic in high concentrations, it is applied by mixing with oxygen at nontoxic concentrations. The concentration range of ozone for clinical application in humans is 1 to 40 μg per mL of oxygen.…”
Section: Introductionmentioning
confidence: 99%